2018
DOI: 10.1007/s11119-018-9612-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in commercial orange groves. Part 1: canopy volume and height

Abstract: 11Characterizing crop spatial variability is crucial for estimating the opportunities for site-12 specific management practices. In the context of tree crops, ranging sensor technology has 13 been developed to assess tree canopy geometry and control real-time variable rate 14 application of plant protection products and fertilizers. The objective of this study was to 15 characterize the variability of canopy geometry attributes in commercial orange groves in 16 Brazil and therefore estimate the potential im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The plant height was spatially correlated for longer distances than the plant canopy temperature for both years (see range parameters in Table 3). Maps derived from kriging indicated that the plot could be divided into zones, which was consistent with other researchers using on-the-go sensors to measure plant canopy height and volume [21]. The differences in plant height observed on the maps were verified during ground-truthing of the field, thus justifying accuracy and potential use of the system as a survey tool.…”
Section: Discussionsupporting
confidence: 87%
“…The plant height was spatially correlated for longer distances than the plant canopy temperature for both years (see range parameters in Table 3). Maps derived from kriging indicated that the plot could be divided into zones, which was consistent with other researchers using on-the-go sensors to measure plant canopy height and volume [21]. The differences in plant height observed on the maps were verified during ground-truthing of the field, thus justifying accuracy and potential use of the system as a survey tool.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatives to the field inspections aimed at verifying the proper completion of these tasks have arisen to overcome this problem in the last years. For example, accurate three-dimensional (3D) modeling and characterization of crop canopies have been achieved using different technologies, such as aerial photogrammetry by means of unmanned aerial vehicles (UAVs) acquired images [4,5], and also LIDAR (light detection and ranging) [6,7], ultrasonic sensors [8,9], or depth cameras [10,11] for mapping 3D structure in different crops. In an economic study, the use of photogrammetric techniques applied in UAV-images has been reported as the most efficient method to geometrically and accurately characterize a vineyard when compared to LIDAR and depth-camera sensors on board on-ground vehicles [12].…”
mentioning
confidence: 99%
“…By comparing the differences in canopy height, coverage and canopy volume, it was proved that reducing farming could improve crop geometric parameters. Colaço et al [29] obtained the canopy height and volume of the orange garden through point cloud data, proving the spatial variability of the canopy geometry. Among them, the coefficient of variation of the canopy volume was 30% to 40%, and the information can be used in agricultural machinery variable assignments.…”
Section: Introductionmentioning
confidence: 98%